Case Report: Giant Congenital Left Atrial Appendage Aneurysm Presenting With Acute Massive Cerebral Infarction and Refractory Atrial Fibrillation: A Case Report and Literature Review - Li, Rui; Ma, Fei; Guan, Han Xiong; Pan, Yue Ying; Liu, Li Gang; Wang, Dao Wen; Wang, Hong (Frontiers in Cardiovascular Medicine, 2022)
Background: Congenital left atrial appendage aneurysm (LAAA) is a rare cardiac anomaly with a variety of presentations, from being asymptomatic to potentially serious complications such as systemic thromboembolism and atrial tachyarrhythmia. Case presentation: We report a case of congenital giant LAAA in a 35-year-old man presenting with acute massive cerebral infarction and atrial fibrillation (AF) with rapid ventricular rate. The AF was refractory to conventional antiarrhythmic agents as amiodarone and electrical cardioversion, but restored and maintained sinus rhythm after surgical resection of LAAA. The patient remained free of events and was in sinus rhythm during half year follow-up. Conclusions: Giant LAAA has the potential causing serious complications and should be managed surgically in most cases.